Conyza aegyptiaca (L.) Dryand ex. Aiton effect on blood glucose levels in normal albinos rats through oral glucose tolerance test - Akakpo, B. Huguette; Akpovi, Casimir D.; Ahounou Aïkpé, Judith F. (My University, 2017)
Conyza aegyptiaca (L.) Dryand ex. Aiton (C. aegyptiaca) is used in West Africa for diabetes treatment without any scientific study and adequate therapeutic indications. Our previous study shows that C. aegyptiaca extract is nontoxic on larvaes and prevent hepatic glucose liberation in rat. In the present study, we evaluated the acute oral toxicity of C. aegyptiaca aqueous and ethanolic extracts at a unique dose of 300 and 2000 mg/kg body weight (bw). We also determined its effect on blood glucose level by the Oral Glucose Tolerance Test (OGTT) on albinos Wistar rats. Acute oral toxicity showed no mortality and no toxic effect throughout the study. There were no significant changes in glycaemia, creatinine, lipids, AST, ALT and ions Ca 2+ levels when compared to control. OGTT showed that only the aqueous extract at the dose of 500 mg/kg bw normalized blood glucose level 75 min after OGTT induction compared to 60 min for Glybenclamide. Results suggest that C. aegyptiaca aerial part extract is safe and possesses anti-hyperglycemia potential. Further studies are needed to isolate and characterize the plant active component and to test it for diabetes treatment.
Keywords: Conyza aegyptiaca; acute toxicity; OGTT; biochemical parameters.